So give the first one x+6, the second one x, and the third one 3(x+x+6)-4
now the second step, x+(x+6)+(6x+14)=180
now, 8x+20=180
then, 8x=180-20
8x=160
x=160/8
x=20.
therefore the first angle =26, second, 20 and the third 134
2006-11-16 06:33:29
·
answer #1
·
answered by musa 3
·
0⤊
0⤋
Let x = second angle
Then x+ 6 = first angle
So 3(2x+6) -4 = third angle
Adding the three angles we get:
x + x+6 + 6x +18 -4 = 8x +20
Since the sum of the angles is 180 we have :
8x+20= 180
8x= 160
x= 20 = 2nd angle
x+6=20+6 = 26 = first angle
3(2x+6)-4 = 3(2*20 +6)-4=3*46-4=134 = third angle.
This is an easier method than solving three simultaneous equations.
2006-11-16 14:37:51
·
answer #2
·
answered by ironduke8159 7
·
0⤊
0⤋
x = second angle
x + 6 is the first angle
3(x + x+6) - 4 = third angle
x + x + 6 + 3(2x + 6) - 4 = 180
8x + 24 - 4 = 180
8x = 160
x = 20
So the angles are 20, 26, 134
2006-11-16 14:28:55
·
answer #3
·
answered by It's Me! 5
·
0⤊
0⤋
Let's call the angles a, b, c
a = b + 6
c = 3(a + b) - 4
a + b + c = 180
I would substitute for (a + b) into the second equation:
a + b = 180 - c
c = 3(180 - c) - 4
c = 540 - 3c - 4
4c = 540 - 4
4c = 536
c = 134°
Now solve for the other two angles:
a = b + 6
a - b = 6
a + b = 180 - c
a + b = 180 - 134 = 46
Add these together:
2a = 52
a = 26°
Finally solve for b:
a + b = 46
26 + b = 46
b = 20°
So your angles are 26°, 20°, 134° respectively.
2006-11-16 14:26:29
·
answer #4
·
answered by Puzzling 7
·
0⤊
1⤋
x+x+6+3(x+x+6)-4=180
2x+6+3x+3x+18-4=180
8x+20=180
8x=160
x=20
so the angles are 20, 26, and 134
2006-11-16 14:31:47
·
answer #5
·
answered by 7
·
0⤊
0⤋
angle x, y,z
x=y+6
z = 3(x+y)-4
x + y + z = 180
z=3(2y+6)-4
z=6y+14
y+6 + y +6y + 14=180
8y=160
y=20
x=26
z=134
2006-11-16 14:28:44
·
answer #6
·
answered by rawfulcopter adfl;kasdjfl;kasdjf 3
·
0⤊
0⤋
so,
a1 = a2 + 6
a3 = 3(a1 + a2) - 4
a1 + a2 + a3 = 180
you have 3 equations and 3 unknowns... solve the system not gonna do the homework for ya bud
2006-11-16 14:36:07
·
answer #7
·
answered by AresIV 4
·
0⤊
0⤋